Evaluation of bone marrow as a metastatic site of human neuroblastoma. (14th October 2014) - Morandi, Fabio; Corrias, Maria Valeria; Pistoia, Vito
Abstract : Arising from neural crest cells, neuroblastoma (NB) is the most common extracranial pediatric solid tumor. The clinical presentation of NB is heterogeneous, ranging from patients with asymptomatic tumor masses, who require minimal treatment, to patients with metastatic disease who are treated with multimodal therapies. Clinical outcome is also variable, with overall survival ranging from 98% to 100% in infants with stage 1 NB, to less than 30% in patients with stage 4 MYCN ‐amplified NB. More than 50% of patients show metastasis at diagnosis, with the involvement of different vascularized tissues, including the bone marrow (BM). In this paper, we focus on BM infiltration by NB cells, which is considered an adverse prognostic factor. In particular, we discuss the role of different biological factors that may favor the dissemination of NB cells in the BM, such as chromosomic abnormalities, gene amplification, transcription factors, cell‐surface receptors, products of oncogenes, and, more importantly, cytokines and chemokines. In addition, we analyze different techniques to evaluate BM infiltration by malignant cells (i.e., flow cytometry, immunocytochemistry, and quantitative reverse transcriptase polymerase chain reaction). Finally, we review recent data regarding phenotypic and genetic characterization of BM‐infiltrating malignant cells and characterization of the BM microenvironment in NB patients compared to healthy subjects.